2018
DOI: 10.1007/s10067-018-4084-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of relapse rates and risk factors of tapering or stopping pharmacologic therapies in axial spondyloarthritis patients with sustained remission

Abstract: The objectives of this study are to evaluate whether tapering or stopping strategies of pharmacologic therapies are efficacious for maintaining remission in patients with axial spondyloarthritis (axSPA) and to analyze the risk factors of disease relapse. Patients diagnosed as axSPA with ankylosing spondylitis disease activity score based on C reactive protein (ASDAS-CRP) ≤2.0 for at least 3 months were randomized into three groups: continuing non-steroidal anti-inflammatory drugs (NSAIDs) and disease-modifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In PsA, one randomised controlled trial (RCT) showed that continuation of ixekizumab was superior to discontinuation, but the majority of patients with loss of efficacy after discontinuation regained low disease activity (LDA) after reinstatement 10. In axSpA, six RCTs studied fixed dose reduction or discontinuation using different TNFi 11–16. The majority of tapered patients in these studies maintained clinical remission or LDA; or regained it quickly after therapy reinstatement, whereas discontinuation was discouraged due to the risk of flares.…”
Section: Introductionmentioning
confidence: 99%
“…In PsA, one randomised controlled trial (RCT) showed that continuation of ixekizumab was superior to discontinuation, but the majority of patients with loss of efficacy after discontinuation regained low disease activity (LDA) after reinstatement 10. In axSpA, six RCTs studied fixed dose reduction or discontinuation using different TNFi 11–16. The majority of tapered patients in these studies maintained clinical remission or LDA; or regained it quickly after therapy reinstatement, whereas discontinuation was discouraged due to the risk of flares.…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases with patients with long periods of remission, severe or repetitive infections, or who are preparing for pregnancy or surgery, discontinuation of anti-TNF treatment may become necessary. Clinical trials indicate that discontinuation of anti-TNF therapy could lead to rapid relapse in almost all AS patients after several weeks or a few months (8)(9)(10)(11)(12). However, the literature is unclear as to the reason of relapse.…”
Section: Introductionmentioning
confidence: 99%